2004
DOI: 10.1007/978-3-642-18619-6
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals and Inhalation Pathology

Abstract: of the hardcover 1st edition 2004 The use of general descriptive names, registered names, trademarks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.Product liability: The publishers cannot guarantee the accuracy of any information about dosage and application contained in this book. In every individual case the user must check such information by consulting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…4) revealed some oxidative potential for both, although more for Fe 2ϩ , supported by a carbonylation assessment that indicated more ROS-based oxidative damage (42) in bulk enzyme extracts in T. reesei than in P. placenta (Table 1). This might reflect some potential for Fe 2ϩ to auto-oxidize in the presence of molecular oxygen, leading to the production of HO˙in the absence of H 2 O 2 (43). Collectively, these analyses imply that our treatments generated oxidative stress when Fenton reactants were present and that P. placenta enzyme activities were more robustly tolerant to this stress than those of T. reesei.…”
Section: Resultsmentioning
confidence: 79%
“…4) revealed some oxidative potential for both, although more for Fe 2ϩ , supported by a carbonylation assessment that indicated more ROS-based oxidative damage (42) in bulk enzyme extracts in T. reesei than in P. placenta (Table 1). This might reflect some potential for Fe 2ϩ to auto-oxidize in the presence of molecular oxygen, leading to the production of HO˙in the absence of H 2 O 2 (43). Collectively, these analyses imply that our treatments generated oxidative stress when Fenton reactants were present and that P. placenta enzyme activities were more robustly tolerant to this stress than those of T. reesei.…”
Section: Resultsmentioning
confidence: 79%
“…The second order rate constant is 2.1 (±0.34) × 10 7 M –1 s –1 at pH 8.0 (SI) for the reaction between 1 O 2 and APAP, and it is 6.3(±1.0) × 10 7 M –1 s –1 for the reaction between 1 O 2 and TMP at pH 8.0 . Combined with the low steady-state concentration of 1 O 2 , it was expected that the transformations of both APAP and TMP would be only slightly inhibited by NaN 3 , which is normally used to quench 1 O 2 and •OH with high rate constants (2.2 × 10 9 and 1.0 × 10 10 M –1 s –1 for 1 O 2 and •OH). , As the contribution of •OH to the transformation of PhOH was small, the results indicated that 1 O 2 contributed little to the photosensitized transformation of phenol in aerated HA solution. Li et al also observed that 1 O 2 contributed little to the transformation of APAP in other NOM solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent discoveries on non-neuronal cholinergic system as a regulator of skin (patho)physiology have drawn attention to the importance of acetylcholinesterase (AChE) in the human skin 57 , 58 . Apart from the extensively known role of AChE in the termination of nerve impulse transmission at the cholinergic synapses by rapid hydrolysis of the neurotransmitter acethylcholine, the rationale underlying the use of AChE inhibitors in the symptomatic treatment of Alzheimer’s disease 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%